Population-pharmacokinetic/pharmacodynamic model of atractylodes lancea (Thunb.) DC. administration in patients with advanced-stage intrahepatic cholangiocarcinoma: a dosage prediction - Teerachat Saeheng; Juntra Karbwang; Kesara Na-Bangchang (BMC, 2024)
Abstract Background A recent phase 2A clinical study of Atractylodes lancea (Thunb.) DC. (AL) in patients with advanced-stage intrahepatic cholangiocarcinoma (iCCA) demonstrated significant reduction of the risk of tumor progression and mortality with a dose ranging from 1,000 to 2,000 mg. The present study aimed to determine the potential dosage regimen of AL for further phase 2B clinical study. Methods Plasma-concentration time profiles of total AL bioactivity and clinical efficacy in patients with advanced-stage iCCA were obtained from Phase 2 A study. The population pharmacokinetic (pop-PK) model was developed. The pop-PK model and Monte-Carlo (MC) simulation, in conjunction with maximum concentration of AL (Cmax) as a cut-off criterion, was performed and validated with clinical data. The optimal model was used to simulate further dosage regimens and clinical efficacy of AL. Results The pop-PK properties of total AL bioactivity were best described by a compartmental model with zero-order absorption (without delay) and linear clearance. None of the investigated covariates improved model accuracy.The developed pop-PK with MC simulations following once-daily dosing of 1,000 mg and 2,000 mg adequately predicted the clinical efficacy (tumor progression and mortality). The once-daily dose of 2,500 mg is recommended for further phase 2B clinical study due to its relatively high efficacy on tumor progression inhibition (73%) and mortality rate reduction (71%) without excessive number of the administered capsules (23 capsules) and low risk of toxicities (<5%). Conclusions The applied pop-PK model with MC simulation, along with the appropriate cut-off pharmacokinetic parameters, can be used as a potential tool for supporting dosage prediction and selection for clinical studies, and thus reducing the rate of drug development failures. Trial registration www.thaiclinicaltrials.org , WHO ICTRP search, TCTR20210129007 , Registed 29 January 2021.